THE RISE OF DIVORCE AMONG CIVIL SERVANTS, ESPECIALLY GOVERNMENT EMPLOYEES WITH WORK AGREEMENTS (PPPK) - Fitriyani, Neni; Wiguna, Wahyu; Asfar, Andi Hasryningsih; Mubarak, Fajri; Febriana, Moch. Rizky; Agustina, Rizkiana (Yayasan Education and Social Center, 2026)
Divorce is currently a social phenomenon increasingly common across various circles, including the Civil Service (ASN), particularly among Government Employees with Work Agreements (PPPK). Unlike the general public, divorce among ASN follows a special procedure that involves administrative stages, starting at the work unit and BKPSDM, and culminating at the Religious Court. In Serang Regency, this phenomenon needs attention because it affects family stability and ASN performance. Domestic conflicts, poor communication, and the inability to manage problems are the dominant factors leading to divorce. This study aims to analyze the phenomenon of divorce among ASN and PPPK in Serang Regency and to examine the local government's strategic steps to address this issue. The research uses a mixed-methods approach, combining descriptive, qualitative, and quantitative methods. Data was obtained through interviews and secondary data from the Serang Regency BKPSDM. The results show that divorce is influenced by prolonged conflict and ineffective communication, even though mediation efforts have been made. Local governments need to strengthen ongoing guidance and prevention efforts to reduce divorce among civil servants.